Innovative and Digital Approaches in Higher Education for Student Motivation and Sustainable Development Goals (SDGs): A Literature Review - Nina Petrukha; Denis Volskyi; Alina Pomaza-Ponomarenko; Stanislav Poroka; Nataliia Kharchenko (ASEAN Journal of Educational Research and Technology, 2027)
This study reviews innovative and digital approaches in higher education as tools for increasing student motivation and supporting Sustainable Development Goals (SDGs). A literature review method was used by analyzing secondary sources related to digital learning, blended learning, flipped learning, problem-based learning, project-based learning, gamification, creativity development, inclusive education, artificial intelligence, and learning analytics. Innovative and digital approaches can strengthen student engagement, autonomy, critical thinking, creativity, and learning accessibility. Student motivation increases when digital tools are integrated with active pedagogy, inclusive support, meaningful learning experiences, and SDG-oriented educational goals.